Evaluation of castor pistillate lines and analysis of mode of inheritance for resistance to Fusarium wilt disease in castor (Ricinus communis L.) - C. Deepika; S.R. Venkatachalam; A. Yuvaraja; P. Arutchenthil; N. Indra; V. Ravichandran; P. Veeramani; P. Kathirvelan (Current Plant Biology, 2024)
Castor is an industrially economic and valuable oilseed crop cultivated worldwide. There is a constant upsurge in demand for its oil. But wilt caused by Fusarium spp. is a devastating disease that severely affects the productivity depending upon the crop stage. Stable high yielding pistillate lines serve as donors in heterosis breeding programme and for further biotechnological advancements. Genetic characterization of wilt resistance indicated the role of duplicate dominant epistasis in YTP 1 × TMV 5, complementary epistasis in DPC 9 × JP 65 and JP 65 × SKI 215, duplicate recessive epistasis in YRCP 1 × DPC 9. Monogenic recessive nature of wilt resistance was reported in other four cross combinations viz., YRCP 2 × JP 65, SKP 84 × JP 65, YRCP 2 × DPC 9 and YRCP 2 × SKP 84. Magnified images taken using LED phase contrast microscope portrayed the presence of microconidia and macroconidia and Scanning Electron Microscope (SEM) image analysis showed the presence of intact internal cell structures in resistant check (48−1) while the cell structures were disturbed with mycelial growth in the susceptible check (JI 35). Among 21 pistillate lines screened, seven viz., DPC 9, DPC 16, SKP 84, JP 96, GEETA, M 574 and M 619–1 were resistant. By screening P1, P2, F1, F2, BC1F1 (P1) and BC1F1 (P2) generations of eight crosses under field and pot test method, the stable pistillate line DPC 9 was found to be wilt resistant. F1 generation plants expressed 100% susceptibility indicating the recessive nature of wilt resistance. JP 65 × SKI 215 and YRCP 1 × DPC 9 showed the minimum incidence comparing other F2 populations. The backcross (YRCP 1 × DPC 9) × DPC 9 was found to possess the lowest wilt incidence compared to other populations under field and green house condition. Hence the identified lines could be better used to develop wilt resistant high yielding hybrid and for further identifying and introgressing genomic regions conferring wilt resistance to high yielding popular variety through linkage/QTL mapping technique.